OBSTACLES TO THE IMPLEMENTATION OF NOTARY AUTHORITY TO CERTIFY TRANSACTIONS ELECTRONICALLY IN BALI - Ida Bagus Dalem Try Utama Manuaba; I Wayan Wesna Astara; Ida Bagus Agung Putra Santika (NOTARIIL Jurnal Kenotariatan, 2022)
This study aims to examine the implementation and constraints of implementing the authority of a Notary to certify transactions electronically. The type of research used is empirical legal research. This study is analysed by using the theory of authority and the theory of utilitarianism (legal expediency) so as to obtain the conclusion of the discussion study in the form of implementation of electronically certifying transactions by a Notary in the form of legal actions or actions by a Notary in providing ratification of an electronic transaction that has similarities with legalization or waarmerking owned by a Notary conventionally. Based on analysis, it was obtained the results that the authority is attributive because it is obtained directly based on the provisions of Article 15 Paragraph (3) of the UUJN-P so that juridically the Notary has this authority only in its implementation because there is no one guideline due to the absence of further arrangements regarding procedures, procedures and types of notary legal actions that are qualified as certifying transactions electronically. The obstacles faced, namely the implementation of certifying transactions electronically in perspective as evidence, it can be conveyed that electronic documents as evidence of legal actions certifying transactions electronically by Notaries are not yet clear the strength of proof as evidence whether it is qualified as an authentic deed product or is it limited to registering, knowing the existence of documents that are certified as legal actions Notary as legalizing or megewaarmeken.